The politics of cinematic representation of disability: "the psychiatric gaze". (March 2014) - Dawn, Ranjita
Abstract Purpose: Social representations as cultural products rooted in praxis are considered to play dominant role in the structuring of identities or self representations. It is a common belief that people with disabilities analyze their experiences in light of the existing meanings and practices prevalent in society. The paper addresses the matrices of recurring themes in representation of disability and discourses of "normalcy" in films in the nineteenth and twentieth century invoking reductionistic attitude, whereby "disability" becomes a condition subject to neurotypical display and narrative coding in the films in question in the context of India. It will especially seek to analyze the theoretical outlook based on the social model of disability, a perspective that includes specific analyses of the representation of people like themselves in popular culture. Method: A systematic and thorough review of 26 Hindi films ranging from the 1960s to 2010 and six English movies. Apart from these, several books and articles have also been critically reviewed. Result and conclusion: The paper concludes with the argument that the idea of disability in mainstream contemporary cinema has been created and perceived as a speculative fantasy and for public consumption, thus reflecting the current status of people with disabilities as the present preferred "enigmatic" condition. Implications for Rehabilitation Films play significant role in communicating characters which have deep impact on peoples' perspective of persons with disabilities. Filmmakers need to adopt more intensely researched and more sensitized approach in creating movies centering on people with disabilities. Films need to focus more on the potentialities rather than the shortcomings of people with disabilities. Filmmakers need adequate training in order to recognize the needs of the concerned population and adopt appropriate resources and interventions to address various issues for their rehabilitation into the mainstream society.